Upaya Penanggulangan Gizi Buruk pada Balita melalui Penjaringan dan Pelacakan Kasus - Rahma Edy Pakaya, Istiti Kandarina, Akhmadi (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: A total of 1.506 children in Yogyakarta Special District Province suffered from malnutrition. They resided in Gunung Kidul (531 children), Sleman (287 children), Kotamadya Yogyakarta (225 children) and Kulon Progo (190 children). (Wirobrajan was 6th from 18 sub-districts of most frequent incident of malnutrition in Yogyakarta.)Objective: To assess the implementation of case screening and case finding of the children malnutrition through both of Posyandu (Integreted Care Venue) and Polyclinic at Wirobrajan Community Health Center, Yogyakarta.Methods: A descriptive non-analytic, cross-sectional study was carried out. Data were collected from in-depth interview. As respondents were member of team of poor nutrition prevention program. Research was conducted from December 24th 2007 to January 9th 2008 at Wirobrajan Community Health Center, Yogyakarta.Results: Case screening was conducted trough both of active and passive. Active case screening was conducted every two or three months by all of Posyandu in Wirobrajan area. Pasive case screening was conducted by daily health service setting in Community Health Center and based on health cader report. case screening was performed by collect data of children include name and age, measurement of body weight and height, head circumference, rough and smooth motoric ability. After that, documentation and reporting to goverment was made. WHO-NCHS standard was used as standard of malnutrition measurement. After case screening or case reporting, case finding was performed by home visit. Data collected by using of questioner or direct interview to parent. Anthropometric re-measurement can be performed as needed refer to community health center or to the hospital if there is enclosing desease and make dokumentation. This activity is convenience with Guideline of Malnutrition Management in and Community Health Center Setting.Keywords: case screening, case finding, children, malnutrition.